Correlation studies for quantitative traits in sesame (Sesamum indicum L.): Correlation studies for quantitative traits in sesame (Sesamum indicum L.) - S M UMATE, (Journal of Oilseeds Research, 2020)
The genetic variability could be determined with the help of genetic parameters such as genetic coefficient of variation, heritability estimates and genetic advance. The present investigation was therefore planned to evaluate different germplasm lines of sesame with objectives to study the genetic variability and correlation. The observed variability in the chosen 20 genotypes of sesame could be partitioned into heritable (genetic) and non-heritable (nongenetic) components.